Meeting Women Where They Are: Integration of Care As the Foundation of Treatment for At-Risk Pregnant and Postpartum Women. - Thomas, Melanie; Hutchison, Margaret; Castro, Gloria; Nau, Melissa; Shumway, Martha; Stotland, Naomi; Spielvogel, Anna (Maternal & Child Health Journal, 2017)
Purpose In these times of rapidly changing health care policies, those involved in the health care of women, especially during the reproductive years, have a unique and daunting opportunity. There is great potential to positively impact women's health through focus on prevention, attention to addressing disparities, and new focus on the integration of behavioral health care in primary care settings. Description In this report from the field, we suggest that the integration of mental health care into other health services and addressing underlying social needs by partnering with community-based organizations should be a top priority for all settings seeking to provide excellent health care for women. Assessment We describe our experience in a diverse, urban, safety net system to draw attention to four areas of innovation that others might adapt in their own systems: (1) addressing social support and other social determinants of health; (2) tailoring services to the specific needs of a population; (3) developing integrated and intensive cross-disciplinary services for high-risk pregnant women; and (4) bridging the divide between prenatal and postpartum care. Conclusion Women are more likely to be engaged with healthcare during their pregnancy. This engagement, however limited, may be a unique 'window of opportunity' to help them address mental health concerns and implement positive behavior change. Future work should include research and program evaluation of innovative programs designed to serve the entire family and meeting at-risk women where they are.